(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
This paper presents the application of the Integrated Transport Effect Modeling System ITEMS, taking into consideration existing vehicle fleet, traffic flows, and ambient air quality monitoring data. The objective of this study is to estimate the exhausts of CO, NOx, and SO2 released by motor vehicles in relation to predictive traffic policy measures in Kaunas, Lithuania.This study analyses the extent to which some traffic policies and future trends may influence the ambient air pollution in urban environment. Three traffic policy measures such as: i) increase of car parking fee; ii) reduction of car parking places; iii) introduction of dedicated traffic lines for public transport are considered as the case studies to examine the extend to which they could reduce emissions from motor vehicles. At the same time, each policy measure comprises four scenarios including one, which indicates the current situation. The comparative analyses of the influence of different traffic policy measures on vehicle/passenger kilometres travelled and on emissions are presented.